Elevated serum monoclonal and polyclonal free light chains and interferon inducible protein‐10 predicts inferior prognosis in untreated diffuse large B‐cell lymphoma. Issue 4 (10th February 2014) - Witzig, Thomas E.; Maurer, Matthew J.; Stenson, Mary J.; Allmer, Cristine; Macon, William; Link, Brian; Katzmann, Jerry A.; Gupta, Mamta
<x xml:space="preserve">Abstract</x> The detection of serum free light (FLC) is useful in the diagnosis of several hematological diseases. The role and biological relevance of monoclonal or polyclonal FLC elevations in predicting long‐term outcome in diffuse large B‐cell lymphoma (DLBCL) is unknown. We determined the relationship of the type of FLC elevations to outcome, tumor genotype, and pattern of serum cytokine elevations in 276 patients with untreated DLBCL. Elevated FLC was an adverse prognostic factor through 6 years of follow‐up (monoclonal, Event free survival (EFS) HR = 3.56, 95% CI: 1.88–6.76, P <0.0001; polyclonal, EFS HR = 2.56, 95% CI: 1.50–4.38, P = 0.0006). About 73% of DLBCL tumors with monoclonal FLC elevations were activated B‐cell type (ABC) versus 33% from patients with normal FLC. Only ABC‐DLBCL lines secreted kappa FLC in vitro and this secretion could be inhibited by the NF‐κB inhibitor bortezomib. Patients with monoclonal FLC had significantly (all P <0.001) increased serum levels of IL‐12, sIL‐2Rα, IL‐1R, and IP‐10. Patients with polyclonal elevations of FLC had higher levels of IL‐6 (P = 0.033), IL‐8 (P =0.025), sIL2Rα (P = 0.011), and IL‐1R1 (P = 0.041). The combination of elevated FLC and a CXC superfamily chemokine IP‐10 predicted a particularly inferior outcome characterized by late relapse. These increased abnormal FLC and cytokines are potentially useful biomarkers for prognosis and selecting agents for untreated DLBCL. Am. J. Hematol. 89:417–422, 2014. © 2014 Wiley Periodicals, Inc.